MONEY LAUNDERING VIA INTERNET IN GEORGIA - Aleksandre Glonti (European Scientific Journal, ESJ, 2015)
The given article mainly focuses on the money laundering crime conducted using the online gambling websites in Georgia. It offers an insight on the scheme of how advanced computer users transfer finances using digital wallets, avoid attention from the law enforcement bodies, and ultimately withdraw the laundered money. In the end of the article, a reader will find recommendations for the legislative implementations on the national/supernational level to make online fund transaction more transparent process for the law enforcement agencies.